General contact force control algorithm in double-sided incremental forming. Issue 1 (2018) - Ren, Huaqing; Li, Fuhua; Moser, Newell; Leem, Dohyun; Li, Tiemin; Ehmann, Kornel; Cao, Jian
Abstract: The utilization of a supporting tool in Double-Sided Incremental Forming (DSIF) imposes a stabilizing compressive stress through the sheet's thickness, increasing, thereby, the material's formability and fatigue life. However, these favorable effects strongly depend on a steady tool-metal contact condition. This work presents a general DSIF control scheme, which augments the conventional position servo-loop with explicit force feedback control. The algorithm is examined for its robustness and effectiveness using complex geometries with varying curvatures and wall angles. The resulting parts have demonstrated enhanced material formability and geometric accuracy.